Oltzako aldaeraren inguruan (2 – Ihabarko azpialdaera) - Artola, Koldo (Fontes linguae vasconum, 2022)
In a previous work we explained why the speech of Ihabar should be differentiated from the rest of Arakil, based on the opinions of Pedro de Yrizar in this respect. That is, always respecting the dialectal classification of Prince Bonaparte, Yrizar divided the Basque of Arakil into two parts, taking into account the characteristics of the intransitive bipersonal verb forms, which, in the case of Ihabar, departing from those of the rest of its valley, extend as far as Arbizu. In this work we offer several samples of the Basque language of Ihabar; specifically, we present the transcriptions of oral testimonies offered by informants born at the end of the 19th century and the beginning of the 20th century.